PWE-028 Significantly Improved Abdominal Pain (AP) with Linaclotide (LIN) vs Placebo (PBO) in Patients (PTS) with Irritable Bowel Syndrome (IBS) Regardless of Baseline Pain Severity in 2 Phase 3 Trials. (4th June 2013) - Johnston, J; Chey, W D; Lavins, B; Shiff, S J; Kurtz, C; MacDougall, J; Jia, X; Schneier, H; Currie, M
Abstract : Introduction: LIN, a 14-amino-acid, minimally absorbed, guanylate cyclase C agonist (GCCA), significantly improved abdominal and bowel symptoms in 2 Phase 3 IBS with constipation (IBS-C) trials. Previous IBS trials of other therapies showed inconsistent effects of baseline AP severity on efficacy. This post-hoc analysis determined the LIN effect on AP stratified by pt-reported baseline AP severity. Methods: Pts with IBS-C (Rome II criteria) were randomised to LIN 290 μg od po or PBO. Pts rated daily AP at its worst during the previous 24h (11-point scale; 0 = none, 10 = very severe) during Baseline and Treatment Periods. Using pooled 12-wk ITT data from 2 Phase 3 trials, pts were stratified by mean baseline AP score (< 5, ≥5- < 7, ≥7). At each post-randomisation visit pts rated their relief of AP over the past wk vs baseline (7-point balanced scale; 1 = completely relieved, 7 = as bad as I can imagine). The Least Squares (LS) mean change from 2-wk Baseline to 12-wk Treatment Period, % improvement, difference estimates and p-values were calculated (ANCOVA; factors = treatment group, geographic region and study. Covariate = baseline AP). Results: Overall, LIN significantly improved 12-wk AP vs PBO. LIN also led to significant benefit in all 3 baseline stratified AP subgroups, with pain score decreases of 29–36% vs 18–20% for PBO (p < 0.0001; Table); improvement was numerically less in pts with milder (< 5) baseline severity. Baseline AP scores significantly correlated with absolute magnitude of change from baseline improvement in AP (r = 0.26; p < 0.0001) but not with % improvement (r = 0.00; p = 0.9184). Pt-rated relief of AP was significantly improved with LIN vs PBO overall (LS mean 2.9 vs 3.5; p < 0.0001); relief of AP was also seen for all 3 baseline AP subgroups (baseline AP < 5: 2.8 vs 3.4; ≥5- < 7: 2.9 vs 3.5; ≥7: 3.0 vs 3.6; p < 0.0001 for all). Conclusion: LIN led to significant absolute and % improvement in AP vs PBO overall and stratified by baseline AP severity. Absolute magnitude of improvement in AP significantly correlated with baseline AP severity; however, all groups had similar % improvement in AP. Pt-rated relief of AP was consistent across baseline AP severity groups. Support: Ironwood Pharmaceuticals Inc & Forest Laboratories Inc. Editing: CMC funded by Almirall Disclosure of Interest: J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, W. Chey Consultant for: Ironwood Pharmaceuticals and Forest Laboratories, B. Lavins Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, S. Shiff Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, C. Kurtz Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, J. MacDougall Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, X. Jia Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, H. Schneier Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals